STRUKTUR PEMBENTUK PERILAKU MEMILIH MASYARAKAT MAMUJU TENGAH DALAM MEMBERIKAN DUKUNGAN TERHADAP ARAS TAMMAUNI PADA PILKADA TAHUN 2015 - muchlis muchlis; Juanda Nawawi; Sukri Sukri (JIAP (Jurnal Ilmu Administrasi Publik), 2021)
This paper describes the structure forming voting behavior Central Mamuju community in providing support to Aras Tammauni. Structures that shape the behavior of the public choose the reciprocation, emotional, traditions, and economic capital. By using qualitative research methods, this study shows that people give support to Aras Tammauni as a form of payment for services Aras Tammauni, especially the migrants Mamuju Central, from the first set foot in Mamuju Middle society homesteader got a lot of help from Aras Tammauni form economic and security needs. Another aspect is the old ideas (conservatively) Central Mamuju original community of the status of nobility attached to Aras Tammauni, indigenous people believe in Aras Tammauni as heir to the heroism inherited from his father and grandfather Daen Tammauni na Maccerinnai. In addition to having the status of nobility, Aras Tammauni also known by the public as a person who is friendly and humorous, people never hesitate to communicate or ask for help against Aras Tammauni, with a friendly personality and humorous as it can change the emotional connection people with Aras Tammauni that should hesitate because nobility status to be close. Finally, the economic capital Aras Tammauni donated in social activities and to assist the needs of life, the economic capital transmission becomes eligibility for Aras Tammauni moral because society considers such actions are a reflection of the generous and morals.